Nitrogen and phosphorus concentrations in discharge from drained peatland forests are increasing - Nieminen, Mika; Sallantaus, Tapani; Ukonmaanaho, Liisa; Nieminen, Tiina; Sarkkola, Sakari (Elsevier, 2017)
The current understanding, based on previous studies, is that increased discharge nutrient concentrations from boreal peatlands drained for forestry return to similar levels as those of pristine peatlands within about 20 years after their drainage. As an implicit consequence of this finding, it has been assumed that there are no long-term increasing trends in nutrient exports from these peatlands after the establishment of forestry. We analysed discharge total nitrogen (TN) and phosphorus (TP) concentration data from 54 catchments with undrained pristine peatlands and 34 catchments with drained peatlands using data with considerably longer drainage history than in previous studies. Our results agree with previous studies in that discharge TN and TP concentrations in areas drained 20-30 years ago did not differ much from those in pristine sites. However, we also observed that the TN and TP concentrations were increasing with years since drainage of these catchments. Discharge TN and TP concentrations were over two times higher in areas drained 60 years ago when compared with more recently drained areas. Our results challenge the current perceptions by showing that forestry-drained peatlands may contribute to water eutrophication considerably more than previously estimated.
Keywords: peat mineralization; turvemaat; suometsät; ravinnepäästöt; ojitus; vedenlaatu; peatlands; nutrients; drainage; water quality